Blood Meal Induced Regulation of Gene Expression in the Maxillary Palps, a Chemosensory Organ of the Mosquito Aedes aegypti - Hill, Sharon R.; Ghaninia, Majid; Ignell, Rickard (Frontiers in Ecology and Evolution, 2019)
Background Aedes aegypti is a prominent and highly competent vector of several arboviral diseases, including dengue, yellow fever and Zika. Behaviours associated with reproductive feeding, both pre- and post-blood meal, directly influence disease transmission capacity. Odours mediate host seeking pre-blood meal, while post-blood meal females are refractory to host odours for at least 24 h. During this time, flight activity is substantially reduced. Two key host odours, carbon dioxide and (R)-1-octen-3-ol, are detected by the maxillary palps in mosquitoes. In the search for future vector control tools, the identification of genes that are regulated in the maxillary palps between host seeking and 24 h post-blood meal may provide an informative pool of targets. Results The blood meal-induced regulation of chemosensory, neuromodulatory and other signal transduction genes was investigated in the maxillary palps of 24 h post-blood fed Ae. aegypti females, six days after emergence, and compared to host-seeking females of the same age using a transcriptomic approach. Genes-of-interest implicated in the behavioural switch from host seeking to post-blood meal quiescence were identified from multiple gene families investigated: odorant receptors, ionotropic receptors, pickpocket receptors, transient receptor potential receptors, odorant binding proteins, chemosensory proteins, neuromodulators and their receptors, as well as constituents of second messenger signalling pathways. Reflecting the change in transcript abundance of families involved in CO2 signalling, the neural sensitivity to this key kairomone compound was found to decrease in blood fed mosquitoes compare with their on-blood fed counter parts. Conclusions Sensory-associated gene expression is regulated in the maxillary palps of Ae. aegypti females in response to blood feeding. The concerted regulation of multiple genes within the sensory pathways of the maxillary palps likely play a key role in modulating the behavioural changes observed post-blood meal. Future functional characterization of the proteins generated by the genes-of-interest identified in this study may provide both a better understanding of the regulation of gonotrophic feeding and a pool of potential targets for vector control strategies.